Simulation of Solidified Microstructure and Experimental Comparative Study of Twin-Roll Casting Aluminum Alloys - Teng Ma; Junting Zhang; Xiaochao Cui; Xiaosi Sun (Advances in Materials Science and Engineering)
A coupled macro-micro mathematical model of twin-roll casting was established in the study. The continuous solidification process of Al-10Mg aluminum alloys in front of the nip point was numerically simulated by the cellular automaton method and the solidification microstructure, dendritic grain radius, and secondary dendrite arm spacing were obtained through simulation to predict the mechanical property of wedge strips. In order to verify the reliability of the simulation results, the metallographic examination and tensile tests were performed with the as-cast specimens. The results showed that the gain size, the distribution characteristics of various grain regions, dendrite arm spacing, and the yield strengths obtained from simulation were consistent with experimental results.